Advanced Ferroelectric LiNb(1-x)TaxO3 Crystal: Crystal Growth, Crystal Structure, Physical Properties - Roshchupkin, D. V.; Emelin, E. V.; Plotitcyna, O. A.; Fahrtdinov, R. R.; Irzhak, D. V.; Karandashev, V. K.; Orlova, T. V.; Redkin, B. S.; Fritze, H.; Suhak, Yu.
The process of promising ferroelectric LiNb(1-x)TaxO3 crystals growing by Czochralski method is studied. For the first time LiNb0.88Ta0ю12O3 crystals were grown. The composition of the crystals was determined by the method of ion mass spectrometry with inductively coupled plasma. Curie temperature TC=1102C was measured by the method of differential scanning calorimetry. The parameters of the crystal unit cell were measured using high-resolution X-ray diffraction. The crystal unit cell parameters a and c occupy an intermediate position between the corresponding values in LiNbO3 and LiTaO3 crystals. The use of scanning electron microscopy and high-resolution X-ray diffraction allowed to measure the velocity of surface acoustic waves.
Keywords: Physics; Cross-Disciplinary